2001
DOI: 10.1038/sj.bmt.1703201
|View full text |Cite
|
Sign up to set email alerts
|

Tandem transplantation in lymphoma

Abstract: Summary:The majority of poor-risk lymphoma patients are not cured with conventional chemotherapy. There is evidence for the superiority of single high-dose chemotherapy in such patients, but many still die from recurrent disease. Strategies to improve survival in these poor-risk patients include dose-intensification with high-dose chemotherapy and PBPC support, tandem autologous HDC with PBPC support, and autologous followed by non-myeloablative allogeneic transplantation. These more aggressive strategies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…10 Autologous HSCT for tumor debulking followed by RIC HSCT has been advocated as a novel concept for patients with advanced lymphoma, providing the tumor reduction before HSCT and giving the necessary time for the GvL-effect to develop. [11][12][13] Results of a planned interim analysis after 10 patients with relapsed/refractory lymphoma treated with BEAM HDC for initial cytoreduction without autologous stem-cell rescue, followed by RIC allogeneic HSCT at day 28 after BEAM have been previously published. 14 Our report showed that the prolonged aplasia with this regimen was manageable, but infectious complications were frequent.…”
Section: Introductionmentioning
confidence: 99%
“…10 Autologous HSCT for tumor debulking followed by RIC HSCT has been advocated as a novel concept for patients with advanced lymphoma, providing the tumor reduction before HSCT and giving the necessary time for the GvL-effect to develop. [11][12][13] Results of a planned interim analysis after 10 patients with relapsed/refractory lymphoma treated with BEAM HDC for initial cytoreduction without autologous stem-cell rescue, followed by RIC allogeneic HSCT at day 28 after BEAM have been previously published. 14 Our report showed that the prolonged aplasia with this regimen was manageable, but infectious complications were frequent.…”
Section: Introductionmentioning
confidence: 99%
“…The CR rate for poor-risk and relapsed patients undergoing tandem therapy may be improved, but a clear demonstration of clinical benefit with acceptable long-term toxicity is necessary before tandem transplantation becomes a viable therapeutic choice over the current approaches to poor-risk patients. 20 Although not tested in a randomized fashion, when used as consolidative therapy in responding poor-risk patients, Haioun et al 12 concluded that tandem transplant did not improve on the results of patients receiving a single consolidative HDC regimen. HDC regimens that include newer targeted therapeutic modalities such as rituximab offer the possibility of improved efficacy and decreased toxicity.…”
Section: Discussionmentioning
confidence: 99%